Assessment of individual kidney function in a dog with congenital anomalies of the urinary tract. Issue 2 (16th April 2019) - Heier, Evelyn; Urban, Christine; Abdellatif, Ahmed; Thiel, Cetina; Neiger, Reto
Abstract : A 21‐month‐old entire female labrador retriever was presented for polyuria, pollakiuria, haematuria and intermittent urinary incontinence. Clinical signs were absent during antibiotic treatment but reoccurred shortly after completion of a treatment course. Investigations detected bilaterally dilated ureters, right renal hypoplasia, left extramural ectopic ureter and right intramural ectopic ureter forming an ureterocoele. Blood tests revealed moderate renal azotaemia. 99m Tc‐DMSA (technetium‐99m‐dimercaptosuccinic acid) scintigraphy was used to quantify individual kidney function to carefully consider nephrectomy. The right kidney contributed to less than 2 per cent of the total kidney function. Individual kidney function assessed by 99m Tc‐DMSA scintigraphy was compared with CT‐based renal parenchyma volume as an equivalent to kidney function. In this case both diagnostic imaging techniques resulted in similar individual kidney function percentages. A right‐sided nephroureterectomy and a left‐sided neoureterocystostomy were performed. Surgical treatment successfully resolved the clinical signs. After surgery the dog's chronic kidney disease remained stable at International Renal Interest Society chronic kidney disease stage 3.